Impact of Internal Practices on Organizational Performance: A Review and Research Agenda in the Pakistan Banking Sector - Ahmed, Ammar; Lebai Othman, Ismail; Qureshi, Muhammad Asif (2017)
Investigation in organizational performance issues is becoming an important research agenda in the recent times.Considering this research agenda, the aim of the current study is to propose the novel conceptual model signifying the impact of organizational internal practices like organizational culture and organizational internal market orientation on the organizational performance in the perspective of organizational commitment as a mediator.Based on the relevant literature review, five research propositions have been framed.Also, the current study indicated the linkages and interactions that take place between organizational behavior and marketing concepts and its consideration at the organizational level which affects the organizational commitment leading to organizational performance.The two underpinning theories (i) Resource Based View (RBV) and (ii) Social Exchange Theory (SET) underpinned the proposed conceptual model.This investigation recommends that the Pakistan banking organizations should focus on their organizational culture and organizational internal market orientation as a strategy and implement them to meet their employees and bank goals. This implementation of the strategies will influence the organizational commitment and in turn enhance the organizational performance.Considering the current situation of the Pakistan banking sector, this study is expected to generate very useful insight for the future researchers, policy makers, branch managers and the regulatory authorities.